EFFECT OF DIABETES TRAINING PROGRAM ON KNOWLEDGE AND ASSESSMENT SKILL AMONG GERIATRIC WORKER COMMUNITY IN SURABAYA - Zamrotul Izzah; Mahardian Rahmadi; Dewi Wara Shinta; Toetik Aryani; Aniek Setiya Budiatin (Universitas Airlangga, 2017)
The prevalence of diabetes mellitus (DM) is higher among other degenerative diseases in Surabaya, Indonesia. Providing information is not suﬃcient to improve diabetic patients’ compliance and achieve goals of its therapy. Patients’ good awareness as well as emotional and social supports from community plays an important role to improve their compliance and clinical outcomes. Therefore, diabetes training program was delivered to geriatric worker community to improve their knowledge on DM and assessment skill to check the blood glucose level of geriatric diabetic patients. A total of 20 female workers were enrolled in the program. They received a series of lectures on diabetes and its management and gained practical skill on using the self-check blood glucose test. A validated questionnaire was administered to all workers at baseline and at final follow-up to assess knowledge and practice. The overall workers’ awareness increased over than 100%. After finishing the program, all workers joined a diabetic counseling program for geriatric patients in their community. Glucose levels were evaluated from their patients to assess the outcome of the counseling program. The random and fasting blood glucose levels decreased around 31% and 14%, consecutively. This study reveals that diabetes training program for geriatric community workers is beneficial to control blood glucose levels. AbstrakDiabetes melitus (DM) merupakan penyakit degeneratif yang memiliki prevalensi lebih tinggi di antara penyakit degeneratif lainnya di Surabaya, Indonesia. Pemberian informasi saja masih dirasakan belum cukup untuk memperbaiki tingkat kepatuhan pasien diabetes dan mencapai tujuan terapi. Kesadaran pasien serta dukungan emosional dan sosial dari masyarakat berperan penting untuk meningkatkan kepatuhan dan hasil terapi. Oleh karena itu, program pelatihan diabetes dilakukan kepada komunitas pekerja lanjut usia (lansia) untuk meningkatkan pengetahuan mereka tentang penyakit DM dan ketrampilan dalam pemeriksaan kadar glukosa darah. Sebanyak 20 orang pekerja perempuan ikut serta sebagai peserta dalam program ini. Mereka menerima serangkaian materi tentang penyakit DM dan pengelolaannya, serta mendapatkan praktek keterampilan untuk menggunakan tes glukosa darah secara mandiri. Sebagai evaluasi kegiatan, kuesioner diberikan kepada peserta pada awal dan akhir kegiatan. Kesadaran pekerja secara keseluruhan meningkat lebih dari 100%. Setelah akhir kegiatan, semua peserta bergabung dengan program konseling diabetes untuk pasien lansia di komunitas mereka. Tingkat glukosa dievaluasi dari pasien mereka untuk menilai hasil program konseling. Tingkat glukosa darah acak dan puasa menurun sekitar 31% dan 14%, berturut-turut. Studi ini mengungkapkan bahwa program pelatihan diabetes untuk pekerja komunitas lansia ini sangat bermanfaat untuk mengendalikan kadar glukosa darah di komunitas.